Fast Neutron and Gamma-Ray Attenuation Properties of Some HMO Tellurite-Tungstate-Antimonate Glasses: Impact of Sm3+ Ions - Ghada ALMisned (MDPI AG, 2021)
Characteristics of tellurite-tungstate-antimonate glasses containing heavy metal oxide were investigated in detail using two methods: the MCNPX Monte Carlo code and the Phy-X/PSD platform. The influence of Sm2O3, translocating with TeO2 at ratios of 0.2, 0.5, 0.8, 1, and 1.5 mol% on radiation shielding properties of glasses, was set forth with five glass structures determined according to the (75-x)TeO2-15Sb2O3-10WO3-xSm2O3 glass composition. Densities of the glasses were prepared by doping a low ratio of Sm2O3 that varied between 5.834 and 5.898 g/cm3. Sample densities, which have an important role in determining radiation shielding character, increased depending on the increase in Sm2O3 concentration. Effective removal cross-section (∑R) values against fast neutrons, as well as linear and mass attenuation coefficients, half-value layer, mean free path, variation of effective atomic number against photon energy, exposure, and energy built-up factors, were simulated with the help of these two methods. As a result of these estimates, it can be concluded that values obtained using both methods are consistent with each other. From the obtained values, it can be concluded that the SM1.5 sample containing 1.5 mol% would have the most efficient role in radiation shielding. An increase of Sm2O3 resulted in a significant increase in linear and mass attenuation coefficients and effective removal cross-section values belonging to fast neutrons and, in addition, resulted in a decrease in the half value layer. Doping HMO glasses with Sm2O3 was observed to contribute directly to the development of radiation shielding properties of the glass.